2020
DOI: 10.1038/s41598-020-67481-w
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale trace metal imprinting of biocalcification of planktic foraminifers by Toba’s super-eruption

Abstract: Bioactive metal releases in ocean surface water, such as those by ash falls during volcanic super-eruptions, might have a potentially toxic impact on biocalcifier planktic microorganisms. Nano-XRF imaging with the cutting-edge synchrotron hard X-ray nano-analysis ID16B beamline (ESRF) revealed for the first time a specific Zn- and Mn-rich banding pattern in the test walls of Globorotalia menardii planktic foraminifers extracted from the Young Toba Tuff layer, and thus contemporaneous with Toba’s super-eruption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In specimens of the benthic Rosalina leei subjected to inorganic mercury (HgCl 2 dissolved in seawater) the growth rate and maximum size decreased considerably (Nigam et al., 2009; Saraswat et al., 2004). Specimens of Globorotalia menardii extracted from the Young Toba Tuff layer (74,000 years ago) show incorporation of trace metals in the wall but no test‐size reduction (Lemelle et al., 2020). As planktic foraminifera from ETM2 are all extinct forms we cannot evaluate a possible negative impact of trace metals on their test‐size.…”
Section: Environmental Context Across the Etm2 And Drivers Of Tethyan...mentioning
confidence: 99%
“…In specimens of the benthic Rosalina leei subjected to inorganic mercury (HgCl 2 dissolved in seawater) the growth rate and maximum size decreased considerably (Nigam et al., 2009; Saraswat et al., 2004). Specimens of Globorotalia menardii extracted from the Young Toba Tuff layer (74,000 years ago) show incorporation of trace metals in the wall but no test‐size reduction (Lemelle et al., 2020). As planktic foraminifera from ETM2 are all extinct forms we cannot evaluate a possible negative impact of trace metals on their test‐size.…”
Section: Environmental Context Across the Etm2 And Drivers Of Tethyan...mentioning
confidence: 99%
“…Ash fallouts from volcanic super-eruptions have a potentially toxic impact on biocalcifier planktic microorganisms. Lemelle et al 39 demonstrated a method to detect past bioactive metal releases in ocean surface water . The use of nanoXRF imaging revealed successfully a specific Zn- and Mn-rich banding pattern in the test walls of Globorotalia menardii planktic foraminifers extracted from the Young Toba Tuff layer which corresponded to Toba’s super-eruption 74 000 years ago.…”
Section: Synchrotron and Large-scale Facilitiesmentioning
confidence: 99%
“…Davis et al (2020) relate the foraminiferal Mn/Ca to deep-water upwelling. Another study suggests Mn-incorporation into the planktic foraminifer shell by volcanogenic input from the Toba super-eruption (Lemelle et al, 2020).…”
mentioning
confidence: 99%